2013
DOI: 10.1007/s11356-013-1904-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of phenols and pharmaceuticals in municipal wastewaters from Polish treatment plants by ultrasound-assisted emulsification–microextraction followed by GC–MS

Abstract: A method combining ultrasound-assisted emulsification–microextraction (USAEME) with gas chromatography–mass spectrometry (GC–MS) was developed for simultaneous determination of four acidic pharmaceuticals, ibuprofen, naproxen, ketoprofen, and diclofenac, as well as four phenols, 4-octylphenol, 4-n-nonylphenol, bisphenol A, and triclosan in municipal wastewaters. Conditions of extraction and simultaneous derivatization were optimized with respect to such aspects as type and volume of extraction solvent, volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 33 publications
(53 reference statements)
0
25
0
1
Order By: Relevance
“…A number of APIs have been detected in the influents and effluents of wastewater treatment plants with the greatest survival rate displayed by carbamazepine (concentrations up to 5128 ng dm ) and naproxen (up to 117,000 ng dm -3 ) which reflects the popularity of these non-steroidal anti-inflammatory drugs in Poland (Kotowska et al 2014). All in all, these findings unsurprisingly indicate that treated wastewater is an important route for the introduction of various xenobiotic pharmaceuticals to surface and groundwater.…”
Section: The State-of-art For Pharmaceutical Pollution Of Water Resoumentioning
confidence: 99%
“…A number of APIs have been detected in the influents and effluents of wastewater treatment plants with the greatest survival rate displayed by carbamazepine (concentrations up to 5128 ng dm ) and naproxen (up to 117,000 ng dm -3 ) which reflects the popularity of these non-steroidal anti-inflammatory drugs in Poland (Kotowska et al 2014). All in all, these findings unsurprisingly indicate that treated wastewater is an important route for the introduction of various xenobiotic pharmaceuticals to surface and groundwater.…”
Section: The State-of-art For Pharmaceutical Pollution Of Water Resoumentioning
confidence: 99%
“…Because pharmaceuticals are in general polar, non-volatile molecules, derivatization reactions are required to make them suitable for GC analysis. To simplify and make this laborious process less time consuming, derivatization is sometimes conducted simultaneous with the sample preparation [81]. In order to enable multi-residue analysis, Kumirska et al [84] introduced a derivatization approach, which allows the simultaneous analysis of pharmaceuticals from six different drug classes in the nanogram per litre range.…”
Section: (I) State-of-the-art Chromatographymentioning
confidence: 99%
“…Kotowska et al [21] reported an USAEME method for the simultaneous determination of four phenols and four pharmaceutical compounds in wastewater from a Polish WWTP. In this work, five different solvents were examined: three with density higher than water (i.e., 1,2-dichlorobenzene, carbon tetrachloride and chloroform) and two lighter than water (i.e., n-decane and toluene).…”
Section: Page 3 Of 19mentioning
confidence: 99%
“…With in-situ derivatization, the reaction is performed simultaneously with the extraction procedure at very mild conditions and in a very short time. The derivatization reagent {i.e., acetic anhydride [21] or methyl chloroformate [22]} is added together with the extraction solvent before the emulsification step.…”
Section: Page 3 Of 19mentioning
confidence: 99%